Retraction: 'Amelioration of Osteoporosis and Hypovitaminosis D by Sunlight Exposure in Hospitalized Elderly Women With Alzheimer's Disease: A Randomized Controlled Trial'. (30th October 2015) - Sato, Yoshihiro; Iwamoto, Jun; Kanoko, Tomohiro; Satoh, Kei
Abstract : The above article, published online on 4 April 2005 in Wiley Online Library (wileyonlinelibrary.com ), and in JBMR Volume 20, Issue 8, pages 1327–1333, together with a subsequent Expression of Concern published online in JBMR on 24 June 2015, has been retracted by agreement between the authors, the Journal Editor in Chief, Juliet Compston, and Wiley Periodicals, Inc. The retraction has been agreed due to duplication of text and concerns about the underlying data to which the authors have given no satisfactory response. Dr. Sato acknowledges that his co‐authors are named as such for honorary reasons and are not responsible for the content of the manuscript. References 1. Sato Y, Iwamoto J, Kanoko T, Satoh K. Amelioration of osteoporosis and hypovitaminosis D by sunlight exposure in hospitalized, elderly women with Alzheimer's disease: A randomized controlled trial. J Bone Miner Res. 2005; 20:1327–33. DOI:10.1359/JBMR050402 . 2. Sato Y, Iwamoto J, Kanoko T, Satoh K. Expression of concern: Amelioration of osteoporosis and hypovitaminosis D by sunlight exposure in hospitalized elderly women with Alzheimer's disease: A randomized controlled trial. J Bone Miner Res. 2015; 30:1745. DOI:10.1002/jbmr.2583 .